2018
DOI: 10.1038/s41467-018-06819-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the intensity of sensory input by two glutamate receptors in one C. elegans interneuron

Abstract: How neurons are capable of decoding stimulus intensity and translate this information into complex behavioral outputs is poorly defined. Here, we demonstrate that the C. elegans interneuron AIB regulates two types of behaviors: reversal initiation and feeding suppression in response to different concentrations of quinine. Low concentrations of quinine are decoded in AIB by a low-threshold, fast-inactivation glutamate receptor GLR-1 and translated into reversal initiation. In contrast, high concentrations of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…[71] As NCS-1 regulates synaptic communication of the presynaptic inhibitory AIY neuron projections in C. elegans, [70,72] targeted regulation of inhibitory neuron communication might enable the emergence of adaptive sensorimotor transformation. [74] In postsynaptic neurons, compartmentalization is an important computational feature and is likely to be a conserved mechanism for signal processing. [73] The inhibitory connections between the AIY interneuron and AIZ provide a means to control the direction of movement, while the excitatory connection between AIY and AIB allows the speed of movement to be modified.…”
Section: Rudimentary Neural Circuits That Mediate Sensorimotor Computmentioning
confidence: 99%
“…[71] As NCS-1 regulates synaptic communication of the presynaptic inhibitory AIY neuron projections in C. elegans, [70,72] targeted regulation of inhibitory neuron communication might enable the emergence of adaptive sensorimotor transformation. [74] In postsynaptic neurons, compartmentalization is an important computational feature and is likely to be a conserved mechanism for signal processing. [73] The inhibitory connections between the AIY interneuron and AIZ provide a means to control the direction of movement, while the excitatory connection between AIY and AIB allows the speed of movement to be modified.…”
Section: Rudimentary Neural Circuits That Mediate Sensorimotor Computmentioning
confidence: 99%
“…Yue et al, 2018;Zou et al, 2018). Briefly, day 2 adult worms were glued on the surface of 757 Sylgard-coated coverslips using the cyanoacrylate-based glue (Gluture Topical Tissue Adhesive, 758Abbott Laboratories).…”
mentioning
confidence: 99%
“…Quantitative analysis of chemotaxis revealed that klinokinesis was disrupted in clh-1(pe572) and clh-1(pe577) mutants upon increase in salt concentration (Figure 6 b , Figure 6—figure supplement 1 b ). To further gain insight into the neural mechanism of this phenomenon, we focused on AIB, a postsynaptic interneuron of ASER which promotes sensory stimulus-dependent reversals, the trigger of pirouettes (Piggott et al, 2011; Zou et al, 2018). Because the synapse between ASE and AIB is proposed as the site of plasticity that regulate klinokinesis bias in salt chemotaxis (Kunitomo et al, 2013; Luo et al, 2014; Wang et al, 2017), we hypothesized that the responsivity of AIB may be altered in these mutants.…”
Section: Resultsmentioning
confidence: 99%
“…ASER makes synapses to three first layer interneurons, AIA, AIB and AIY. Activation of AIA and AIY are known to promote forward locomotion, while activation of AIB promotes reversals (Gray et al, 2005; Piggott et al, 2011; Zou et al, 2018). Also, salt response of AIB is markedly changed by salt experience.…”
Section: Discussionmentioning
confidence: 99%